Surveillance for Leishmania asymptomatic infection in endemic foci of cutaneous leishmaniasis in Venezuela: a combination of leishmanin skin test and PCR using blood clots improves detection and enables identification of species. (23rd January 2020) - Torrellas, Annhymariet; Ferrer, Elizabeth; Cruz, Israel; De Lima, Hector; Borges, Rafael; Delgado, Olinda; Moffi, Pablo; Miles, Michael A; Feliciangeli, M Dora
Abstract: Background: Little is known about the prevalence of asymptomatic leishmaniasis in Venezuela. The objective of this study was to quantify Leishmania asymptomatic infection in six endemic foci of cutaneous leishmaniasis (CL) in Portuguesa State, Venezuela, where no previous data were available. Methods: Study of the prevalence of Leishmania asymptomatic infection was carried out in 841 individuals from six endemic foci of CL in the municipalities Sucre and Ospino, Portuguesa State. We applied the leishmanin skin test (LST) and the internal transcribed spacer 1 (ITS1) PCR to DNA from sera and blood clots of all LST-positive and 20% of LST-negative patients. Results: Of 841 inhabitants tested by LST, 197 returned a positive reaction (23.42%); all of the LST-positives (197) and 121 negatives were screened by nested PCR using serum and blood clots. Among the LST-positive group, 2.54% were PCR-positive with sera, while 44.67% were positive with blood clots. In the LST-negative group, PCR was positive in 2.48% of serum samples and in 38.84% of blood clots. Conclusions: It is recommended that LST and PCR on blood clots are used together to detect exposure and asymptomatic infection and for identification of the Leishmania species.